Repercussions des activites humaines dans les collocations verbo-nominales - Vetulani, Grażyna (Neophilologica, 2005)
In the paper we focus on the relationship between knowledge and the world. We address this issue through the study of the class of verb + noun collocations. We notice that valid classifications of human behavior may be based on properties of the verb constituents of such structures. Verb + noun collocations appear to be a useful tool for the design of linguistically motivated ontologies.